Research methods science and diversity - Spata, A V (New York : John Wiley, 2003)
"Research Methods in Psychology: Science and Diversity" by Andrea V. Spata offers a unique approach to research methods by integrating cross-cultural perspectives throughout. It uses an experimental approach, covering core research principles within psychology. The book's strength lies in weaving cultural considerations into each stage of the research process, rather than treating it as a separate topic. This helps students understand how culture influences research design, data collection, and interpretation. It likely covers topics like research design, statistical analysis, and ethical considerations, all with a cross-cultural lens. The integrated approach aims to produce more culturally sensitive and robust research. It emphasizes the importance of understanding cultural influences on psychological research. This book is useful for psychology students seeking a culturally informed understanding of research methods. It likely provides practical guidance on conducting culturally sensitive research. The book stands out for its focus on diversity and cross-cultural issues in research.
Includes appendix, glossary, bibliographical references (p. 323-328) and index.
Keywords: Research methods in science and diversity studies; Science and diversity studies